Using social media for assessment purposes: Practices and future directions - Alonzo, Dennis; Oo, Cherry Zin; Wijarwadi, Wendi; Hannigan, Caitlin (Frontiers in Psychology, 2023)
The use of social media across the world is rapidly increasing, and schools are advancing its use for learning, teaching, and assessment activities. Despite growing evidence for their accessibility and affordances for educational purposes, very little attention has been paid to their use in assessment. Using the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA), this paper is an initial step to explore how social media have been used and reported in the literature, and describe some key challenges. A total of 167 articles were initially accessed from three databases, but only 17 were relevant after applying the exclusion criteria. Results show that the most dominant social media used in assessment are Facebook and Twitter. Also, the assessment practices are limited to sending and discussing assessment tasks, following up on progress, giving feedback, and engaging in self and peer assessment. Key issues include the trustworthiness of the assessment process and outputs, limited features of social media platforms, technical support, time commitment between teachers and students, and intersections of social and academic engagements. We discuss the implications of these findings with the critical gaps in the theorisation of using social media for assessment purposes.